2015
DOI: 10.1089/fpd.2015.1960
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Resistance to Broad-Spectrum Cephalosporin in Escherichia coli from Healthy Broilers at Farms in Japan After Voluntary Withdrawal of Ceftiofur

Abstract: The high prevalence of broad-spectrum cephalosporin (BSC) resistance in Escherichia coli isolates from healthy broilers at farms is a source of grave concern in Japan. In an effort to solve this problem, the off-label use of ceftiofur (CTF) at hatcheries was voluntarily withdrawn around March 2012. The objective of this study was to assess the effect of the voluntary withdrawal on the prevalence of BSC resistance in E. coli from healthy broilers at farms. A total of 693 E. coli isolates collected from 362 feca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 10 publications
2
35
0
Order By: Relevance
“…Examination of the indicator E. coli in our study clearly demonstrates a decrease in prevalence of samples harboring isolates positive for the ESBL/AmpC resistance genes bla CMY-2 and bla CTX-M in the meconium of newly hatched birds after the cessation of in ovo administration of ceftiofur. This finding shows a beneficial effect of the cessation of the use of ceftiofur, reinforcing the findings of other studies where a decrease in resistance to extended spectrum cephalosporins was observed (4, 9, 12). Nevertheless, we did not observe an effect in the broilers, as was the case in the previous studies (7).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Examination of the indicator E. coli in our study clearly demonstrates a decrease in prevalence of samples harboring isolates positive for the ESBL/AmpC resistance genes bla CMY-2 and bla CTX-M in the meconium of newly hatched birds after the cessation of in ovo administration of ceftiofur. This finding shows a beneficial effect of the cessation of the use of ceftiofur, reinforcing the findings of other studies where a decrease in resistance to extended spectrum cephalosporins was observed (4, 9, 12). Nevertheless, we did not observe an effect in the broilers, as was the case in the previous studies (7).…”
Section: Discussionsupporting
confidence: 90%
“…One of the most important causes of early mortality in broiler chick is omphalitis, mostly caused by avian pathogenic E. coli (APEC), a subgroup of extra-intestinal pathogenic E. coli (ExPEC) (1, 2). Ceftiofur, a third generation cephalosporin antimicrobial, has been administered for over 15 years either in ovo or by subcutaneous injection at the hatchery, in order to reduce early chick mortality in many countries (3) Consequently, an increased prevalence of extended-spectrum β-lactamase (ESBL) and AmpC β-lactamase producing Escherichia coli has been reported worldwide (4-7), resulting in an increased extended spectrum cephalosporin resistance in the broiler poultry chain production. This is a public health concern due to co-resistance with other extended spectrum cephalosporins, such as ceftriaxone and cephamycin, antimicrobials which are used widely in human medicine (8, 9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent Canadian studies have shown a decrease in the proportion of clinical isolates possessing ESBL/AmpC-associated resistance genes after the second cessation in 2014 (13)(14)(15). In addition, the prevalence of resistant E. coli from healthy broilers on farms was decreased within a year after ceftiofur cessation at hatcheries in Japan, from 16.4% in 2010 and 16.8% in 2011 to 9.2% in 2012 and 4.6% in 2013 (4). A decrease in the prevalence of Salmonella harboring bla CMY-2 in chicken meat was also observed in Japan in the same years (16).…”
mentioning
confidence: 84%
“…Ceftiofur, a third-generation cephalosporin antimicrobial, has been administered for over 15 years either in ovo or by subcutaneous injection at the hatchery, in order to reduce early chick mortality in many countries (3). Consequently, an increased prevalence of extended-spectrum-␤-lactamase (ESBL) and AmpC ␤-lactamase-producing Escherichia coli has been reported worldwide (4)(5)(6); this increased prevalence has resulted in an increased resistance to extended-spectrum cephalosporins in the broiler poultry production chain. This is a public health concern due to cross-resistance with other extended-spectrum cephalosporins, such as ceftriaxone and cephamycin, antimicrobials that are used widely in human medicine and classified by the World Health Organization as highest-priority critically important antimicrobials (7)(8)(9)(10).…”
mentioning
confidence: 99%